Cardiac Tissue Engineering: Inclusion of Non-cardiomyocytes for Enhanced Features - Munawar, Sadek; Turnbull, Irene C. (Frontiers in Cell and Developmental Biology, 2021)
Engineered cardiac tissues (ECTs) are 3D physiological models of the heart that are created and studied for their potential role in developing therapies of cardiovascular diseases and testing cardio toxicity of drugs. Recreating the microenvironment of the native myocardium in vitro mainly involves the use of cardiomyocytes. However, ECTs with only cardiomyocytes (CM-only) often perform poorly and are less similar to the native myocardium compared to ECTs constructed from co-culture of cardiomyocytes and nonmyocytes. One important goal of co-culture tissues is to mimic the native heart’s cellular composition, which can result in better tissue function and maturity. In this review, we investigate the role of nonmyocytes in ECTs and discuss the mechanisms behind the contributions of nonmyocytes in enhancement of ECT features.